BERPIKIR POSITIF PADA HADITS “ANĀ ‘INDA ZHANNĪ ‘ABDI BĪ” DALAM PERSPEKTIF GRAMATIKA DAN BALAGHAH - Yusra, Oktarina Rina (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
This study aims to analyze positive thinking in the hadith "ana 'inda zhanni 'abdi bi" in a grammatical and balaghah perspective. The diction of the hadith confirms that Allah will actually realize what His servant thinks of him, both positive and negative because there is taukid namely dhamir al-fashl at the beginning of the hadith and ismiyyatul jumlah which strengthens jumlah khabariyah. However, if it is examined from a grammatical and balaghah perspective, the hadith contains an invitation to think positively, not negatively. This research is library research by examining books and scientific works related to the title. The authors found that the hadith is included in the chapter on the invitation to remember Allah from this study. Allah warns His servants to be careful in prejudice or thinking of Him because He is present, close, closely attached to what is suspected or thought by the servant, and is easily able to realize what is suspected or thought. As a "closeness" and "specialization" for 'abdu (obedient and submissive servant), Allah invites His servants to think positively, remember  Him, draw closer to Him, and come to Him. Then He will reward the servant with good rewards that will lead him to success in this world and the hereafter. In the hadith there are taukid, tahriku al-himmah ila ma yalzamu tahshiluhu, ziyadatu at-taqrir wa al-idhah li as-sami', ta'jilu al-masarrah, azh-zharfu li hudhuri asy-sya'i wa dunuwwihi, al -yaqin billahi, wa at-takhshishu li al-'abdi al-khadhi' li rabbihi al-mustaslimi al-munqadi li amrihi and al-ilshaq. Therefore, every servant should try always to think positively.